The Impact of Online Learning Policy during the Covid-19 Pandemic: An Analysis of Islamic Education - M. Syahran Jailani; Sutrisno Sutrisno; M. Manazil Siddik (INNOVATIO: Journal for Religious Innovation Studies, 2020)
Abstract: This article aims to analyze how the online learning policy launched by the government during the Covid-19 pandemic impact on Islamic religious education. The analysis approach used is a library research and research results related to online learning policies during the Covid 19 period. This research findings show that the implementation of online learning is still far from what is expected, despite all its advantages and disadvantages. The dynamics experienced either by educators, students or parents is a challenge for the government. The collaboration of educational institutions, students and parents is essential for the success of this program. The impact of online learning in the context of Islamic education is very influential in the process of ordering character and inculcating Islamic values. The stakeholders and all policy makers must encourage this policy so that the learning transformation process can be carried out properly, by utilizing and maximizing the presence of information and communication technology availability. Keywords: online learning, covid-19 and Islamic education. Abstrak: Artikel ini bertujuan menganalisis bagaimana dampak kebijakan pembelajaran jarak jauh yang dicanangkan pemerintah di masa pandemi covid-19 pada pendidikan agama Islam. Analisis dengan menggunakan kajian literatur-literatur kepustakaan dan hasil penelitian yang terkait dengan kebijakan pembelajaran jarak jauh jauh di masa Covid 19. Hasil analisis, bahwa implementasi kebijakan pembelajaran jarak jauh dirasakan masih belum sesuai dengan harapan, terlepas dengan segala kelebihan dan kekuranganya. Dinamika yang dihadapi di masa Covid 19 ini oleh pendidik maupun peserta didik serta orang tua menjadi tantangan tersendiri bagi pemerintah. Kolaborasi antara institusi pendidikan, peserta didik dan orang tua sangat diperlukan demi suksesnya program ini. Imbas pembelajaran jarak jauh pada konteks pendidikan Islam sangat berpengaruh dalam proses pembentukan karakter dan penanaman nilai-nilai ke-Islaman. Stake holder dan semua pemangku kebijakan mesti mendorong kebijakan ini agar proses transformasi pembelajaran dapat berjalan baik, dengan memanfaatkan dan memaksimalkan hadirnya teknologi informasi dan komunikasi yang tersedia. Kata-kata Kunci: Pembelajaran jarak jauh, covid-19 dan pendidikan Islam.